1990
DOI: 10.1258/002367790780866263
|View full text |Cite
|
Sign up to set email alerts
|

Growth and liver morphology after long-term ethanol consumption of rats

Abstract: SummaryEthanol was administered to female and male Wistar rats by mixing it with their drinking water. Ethanol concentrations were gradually increased up to either 8% or 15070.Female rats receiving8070 ethanol in their drinking water consumed 5-13 g, males 4-10 g daily. The ethanol/total food caloric intake percentages were 13 to 20070and 9 to 15070for female and male rats, respectively. There was no difference in body weight and relative liver weight between treated rats and their controls.Female and male rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Early, late single hit and double hit with alcohol had no effect on the hepatosomatic index in the present study. In line with our finding, another research group found that alcohol consumption does not affect the hepatosomatic index of rats [ 46 ]. However, in contrast to our findings, other studies showed that alcohol consumption increased liver weight [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…Early, late single hit and double hit with alcohol had no effect on the hepatosomatic index in the present study. In line with our finding, another research group found that alcohol consumption does not affect the hepatosomatic index of rats [ 46 ]. However, in contrast to our findings, other studies showed that alcohol consumption increased liver weight [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…Total monounsaturated fatty acids (MUFA) were decreased in both serum (p<0.05) and liver phospholipids (p<0.001). (20). Some observa tion suggests that alcohol consumption influenced food consumption and weight gain in animals (22).…”
Section: Methodsmentioning
confidence: 99%